Chapter Genoa: Colonizing and Colonized City? The Port City as a Pole of Attraction for Foreign Merchants (16th-18th centuries) - Zanini, Andrea (Atti delle «Settimane di Studi» e altri Convegni, 2019)
As Michel Balard pointed out with reference to the late Middle Ages and to the relations between Genoa and overseas cities, "Genoa, a colonizer in the East, is colonized by the Orientals". The aim of this work is to verify whether and to what extent this concept is applicable also to the modern age and whether it involved a wider geographic area than the one examined by this French historian. In particular we outline the features of the presence of foreign merchants in Genoa between the 16th and 18th centuries as a phenomenon complementary to the better known "diaspora" of Genoese businessmen.